The Influence of Price, Product Quality, and Brand Ambassador on MS Glow Purchasing Decisions - Rahayu, Puji; Yanti, Sri; Auzar, Silvia Revana (Zona Manajerial: Program Studi Manajemen (S1), 2023)
This research aims to determine the influence of price on purchasing decisions for Ms Glow among students at the Faculty of Economics and Business, Batam University, to determine the influence of product quality on purchasing decisions for Ms Glow among students at the Faculty of Economics and Business, Batam University, to determine the influence of Brand Ambassadors on purchasing decisions for Ms Glow. For students at the Faculty of Economics and Business, Batam University, to find out price, product quality and Brand Ambassador together, they influence purchasing decisions for students at the Faculty of Economics and Business, Batam University. The method that the author used in preparing this thesis is a quantitative method with descriptive analysis and multiple linear regression. The population in this study were all students from the Faculty of Economics and Business, Batam University who used Ms Glow products with a total of 162 students. The sample for this research was 116 respondents. Data processing in this research used the SPSS Version 27.0 software program. From the results of calculations and analysis using SPSS Version 27.0 software, the author can draw the conclusion that the Price Variable (X1) has a positive and significant influence on purchasing decisions with a significance value of 0.000 < 0.05. The Product Quality variable (X2) has a positive and significant influence on purchasing decisions with a significance value of 0.000 < 0.05. The Brand Ambassador variable (X3) has a positive and significant influence on purchasing decisions with a significance value of 0.009 < 0.05. The coefficient of determination value of 82.6% shows the contribution of price, product quality and Brand Ambassador to purchasing decisions and the remaining 17.4% is influenced by various other variables.